Períodos de interferência de plantas daninhas na cultura do girassol - da Silva, José Iran Cardoso (2013)
The interference of weeds in sunflower cultivation can significantly reduce the productivity of achenes. The objective of this study was to determine the period before interference and total period of interference of the weed community on productivity and achene oil of sunflower cultivation. The experiment was conducted under field conditions in the fieldin Botucatu (SP) in the 2007/2008 agricultural year. The experimental design was a randomized complete block with four replications. The treatments were composed of portions represent periods of control and presence of weeds. For control periods, the culture was kept free of weeds by increasing periods of 7, 14, 21, 28, 35, 42, 49 and 110 days after the emergence (DAE) of sunflower. For periods of coexistence, the culture was maintained in the presence of the weed community for the same periods. We assessed the following variables: diameter of chapters, achene yield, oil yield of sunflower, density and dry matter of weeds and phytosociological indices. The period before the interference was 35 DAE culture to the productivity of achenes, and the total period of interference lasted until 24 DAE. For oil yield, the period before the interference was 25 DAE, whereas the total period of interference lasted for 14 DAE.